Teh Kombucha Berbasis Rosella (Hibiscus sabdariffa) dan Chia Seed Sebagai Alternatif Minuman Kesehatan - Syafriyana Zaitun; Nadiva Viraniswah; Asmi Wafi Huwaidah; Rina Hidayati Pratiwi (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
One of the functional food products that is often consumed by the public is probiotic drinks. One type of probiotic drink is kombucha. This study aims to explore the potential of kombucha made from roselle flower and chia seeds as a functional and healthy beverage for all age groups. Kombucha is a fermented tea drink enriched with roselle flower, known for its high levels of antioxidants, vitamins, and omega-3, as well as chia seeds, which are rich in fiber, protein, and minerals. The research was conducted in Depok, December 2024 using an experimental method. Data were collected through an organoleptic test involving 20 panelists who assessed the product’s taste, color, and aroma using questionnaires. The results showed an acceptance rate of 65% for taste, 62.5% for color, and 60% for aroma. Fermentation influenced the product’s color and aroma, while taste emerged as the most favorable aspect among panelists. Roselle and chia seed-based kombucha has the potential to be accepted by consumers as a health-promoting beverage that is not only refreshing but also beneficial, such as boosting the immune system and supporting digestion. This study is expected to contribute to the development of natural, functional beverages that support a healthy lifestyle.